Self-administered dual-task training reduces balance deficits and falls among community-dwelling older adults: a multicentre parallel-group randomised controlled trial with economic evaluation protocol - Wai-Chi Chan; Cynthia Huijun Chen; Mohammad Jobair Khan; Kenneth N. K Fong; Thomson Wai-Lung Wong; William Wai-nam Tsang; Stanley Winser (BMJ Open)
Background Falls are common causes of disability, reduced disability-adjusted life years and death in older adults. Balance deficits and cognitive impairment are common causes of falls. Dual-task training is a new strategy that can potentially improve balance and cognitive function, leading to decreased falls. The effectiveness and cost-effectiveness of self-administered dual-task (sDT) training to improve balance and prevent falls is not known. We developed sDT training combining physical and cognitive tasks to improve balance and reduce falls. The proposed randomised controlled trial (RCT) with economic evaluation is to test the effectiveness and cost-effectiveness of the sDT compared with self-administered single-task training (sST) in this population.Methods and analysis In this RCT, we will recruit 190 community-dwelling older adults with a history of at least one fall over the last 6 months from 11 elderly centres. The older adults will be randomly assigned to the sDT (n=95) and sST groups (n=95). Each group will be offered in six training workshops to teach the participants either sDT or sST depending on the group allocation. Each workshop will last an hour and will be held once every 2 weeks for 3 months. Besides, the participants will be instructed to repeat the exercises at home two times weekly for 3 months. Following the intervention phase, the participants will continue unsupervised home-based exercises for 6 months. Assessments will be performed before, after and 6 months after completing the intervention. A fall calendar and cost diary will be provided to each older adult to record the number of falls and fall-related costs during and after the intervention to assess fall incidence and cost-effectiveness. Effectiveness will be assessed using a negative binomial regression model following the intention-to-treat principle for falls and a linear mixed model for the additional measure and cost-effectiveness using a Markov model.Ethics and dissemination This study has ethical approval from the PolyU Institutional Review Board for conducting research on human subjects (Ref: HSEARS20210322005). The results will be disseminated through seminars for individuals and health practitioners, international conferences and published in peer-reviewed journals.Trial registration number NCT05533333.